ANALISA KENAIKAN TCH (TRAFFIC CHANNEL) BLOCKING 2G MENGGUNAKAN NETACT NOKIA PADA AREA RTPO (RADIO TRANSPORT POWER OPERATION) DESA SEDAYU KABUPATEN SAMBAS - Nur Kharisma Jati . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstract TCH Blocking occurs when TCH channel allocation is inefficient to the density of traffic in a network, unavailability of TCH channels are available. Which causes inconvenience customers in making a call. Other factors that also could cause an increase TCH Blocking for problematic Hardware, Coverage inefficient and, Great inequality traffic devices contained in a cell in the network (Unbalanced traffic). Value TCH Blocking a good standard, namely between 0 ≤ 0,5 % standard PT Telkomsel. If the value exceeds the standards TCH Blocking Good, it is necessary to optimal handling. One of them with the analysis parameters via DUMP Nokia (parameter place container). Then analyzed the change of parameters via Nokia NetAct. Nokia NetAct is an automatic tool to improve the quality and performance of the radio network. NetAct allows monitoring, management, and consolidated operating GSM and 3G networks of Telkomsel. As of June 27, 2016 s / d July 2, 2016 there is an increase TCH Blocking in BTS SBS015MG1_SEDAYUMG2 amounted to 0.987%; 10.099%; 1.163%; 1.352% and 0.985%. The increase led to calls experiencing block, because it was the unavailability of the channel TCH provided. After a change in the Channel Type parameter from 3 to 2. TCH rise Blocking problems can be overcome. So the value of TCH Blocking becomes 0,00%, it can be concluded from these values are no longer calls that have failed (Block), because of the unavailability of the available channel TCH. Keywords - TCH Blocking, Blocking, Nokia NetAct, Coverage.